Pharmacotherapy of erectile dysfunction: Current standards - Kew-Kim Chew (Indian Journal of Urology, 2006)
Pharmacotherapy is currently the therapeutic option of choice for erectile dysfunction. Comprising mainly intracavernosal injection therapy using alprostadil or alprostadil combined with phentolamine and/or papaverine and oral phosphodiesterase-5 inhibitors, it is safe and effective if appropriately prescribed and administered. The medications in current use produce satisfactory erectile responses by enhancing cavernosal vasodilatation mainly through their ability to promote relaxation of the smooth muscle cells in the corpora cavernosa involving the synthesis and activity of nitric oxide via the cyclic guanosine monophosphate and cyclic adenosine monophosphate biochemical pathways. The main side-effects and complications of intracavernosal injections are postinjection pain, prolonged erections, priapism and penile fibrosis. There may be a variety of side-effects with phosphodiesterase-5 inhibition but these are usually inconsequential. Recent serious ill health and the need for ongoing long-acting nitrate therapy or frequent use of short-acting nitrates for angina are absolute contraindications to the use of phosphodiesterase-5 inhibitors. Caution has to be exercised in prescribing phosphodiesterase-5 inhibitors for patients with impaired renal or hepatic functions or receiving multi-drug therapy for any systemic disease. All patients presenting with erectile dysfunction should be investigated and treated for cardiovascular risk factors. They should also be counseled regarding lifestyle factors particularly healthy balanced diet, regular physical exercise and inappropriate social habits.